Criminal policy in the legal security system - Ongarbayev, E.A.; Sembejova, Б.Р. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
The article considers issues of legal security through the modernization of criminal law, criminal procedure and criminal execution norms aimed at improving the criminal policy of the Republic of Kazakhstan. The authors carried out an analysis of norms of criminal law, criminal procedural, and criminal executive legislation of the Republic of Kazakhstan. The article highlights some innovations in a comparative aspect, indicating promising directions, ensuring the effectiveness of their application and implementation in law enforcement activity of the subjects of proof. The article reveals mechanisms of criminal policy improvement based on the system-complex approach and application of comparative-legal analysis. System-complex approach has been considered in terms of disclosure of material and procedural norms, determining comprehensiveness, completeness, and objectivity of regular processes of interaction, reflection, and manifestation of objective-subjective factors of formation and development of criminal activity. The mechanism of criminal activity has been disclosed in terms of regulation and management of the process of detection, investigation and prevention based on the principles of legality, objectivity and completeness in the pre-trial and trial processes that determine the factors of implementation of the classification basis of criminal offenses.Comparative legal analysis determined the effectiveness and efficiency of mechanisms to improve criminal policy based on the analysis of theoretical research and practice of foreign countries.